Synchronic historical patterns of species diversification in seasonal aplocheiloid killifishes of the semi-arid Brazilian Caatinga. - Wilson J E M Costa; Pedro F Amorim; José Leonardo O Mattos (PLoS ONE, 2018)
The Caatinga is the largest nucleus of seasonally dry tropical forests in South America, but little is known about the evolutionary history and biogeography of endemic organisms. Evolutionary diversification and distribution of terrestrial vertebrates endemic to the Caatinga have been explained by palaeogeographical Neogene episodes, mostly related to changes in the course of the São Francisco River, the largest river in the region. Our objective is to estimate the timing of divergence of two endemic groups of short-lived seasonal killifishes inhabiting all ecoregions of the Caatinga, testing the occurrence of synchronic events of spatial diversification in light of available data on regional palaeogeography. We performed independent time-calibrated phylogenetic molecular analyses for two clades of sympatric and geographically widespread seasonal killifishes endemic to the Caatinga, the Hypsolebias antenori group and the Cynolebias alpha-clade. Our results consistently indicate that species diversification took place synchronically in both groups, as well as it is contemporary to diversification of other organisms adapted to life in the semi-arid Caatinga, including lizards and small mammals. Both groups originated during the Miocene, but species diversification started between the Late Miocene and Early Pliocene, when global cooling probably favoured the expansion of semi-arid areas. Synchronic diversification patterns found are chronologically related to Tertiary palaeogeographical reorganizations associated to continental drift and to Quaternary climatic changes, corroborating the recent proposal that South American biodiversity has been continuously shaped between the Late Paleogene and Pleistocene.